A Juridical Review of Supreme Court Circular Letter Number 2 of 2024 from the Perspective of Justice and Its Legal Standing in the Tax Court - Santi, Bestari Nirmala; Miracle Kusen, Gabriel Chivalry; Sindra , William Christopher; Anggraini , Yessy (Green Publisher Indonesia, 2025)
This study examines the legal status and justice implications of SEMA 2/2024 in tax dispute cases, particularly regarding the restriction on the use of evidentiary documents in court proceedings. SEMA 2/2024 adopts the provision of Article 26A paragraph (4) of the KUP Law, which prohibits the use of documents not submitted during the audit or objection stage as admissible evidence before the Tax Court. The approach used is normative juridical research by analyzing statutory regulations and court decisions. The findings indicate that SEMA, which does not hold a place within the formal hierarchy of legislation, should not be used to restrict evidentiary rights already guaranteed by Articles 76 and 78 of the Tax Court Law. The provision in SEMA 2/2024 potentially hinders the principle of material truth and disadvantages taxpayers both procedurally and substantively. It also poses a risk of legal uncertainty and violates the principle of lex superior derogat legi inferiori. Therefore, an evaluation of the implementation of this SEMA is necessary to ensure harmony between administrative norms and the principle of justice in tax dispute resolution.